2009
DOI: 10.1007/s00710-009-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Sr–Nd isotope geochemistry of the early Precambrian sub-alkaline mafic igneous rocks from the southern Bastar craton, Central India

Abstract: SummarySr-Nd isotope data are reported for the early Precambrian sub-alkaline mafic igneous rocks of the southern Bastar craton, central India. These mafic rocks are mostly dykes but there are a few volcanic exposures. Field relationships together with the petrological and geochemical characteristics of these mafic dykes divide them into two groups; Meso-Neoarchaean subalkaline mafic dykes (BD1) and Paleoproterozoic (1.88 Ga) sub-alkaline mafic dykes (BD2). The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Their 143 Nd/ 144 Nd i ratios vary between 0.5097 and 0.5102; εNd values correspondingly range from +1 to -10. Sr and Nd isotopic values of similar range are also reported from 1.88 Ga BD2 dykes in Bastar craton (Srivastava et al, 2009) and Bijawar igneous units (Pandey et al, 2012). In a Sr-Nd isotope plot (figure not shown), the Proterozoic mafic samples strikingly differ from the mantle components defined by Hart and Zindler (1989).…”
Section: Geochemistry and Petrological Featuressupporting
confidence: 75%
“…Their 143 Nd/ 144 Nd i ratios vary between 0.5097 and 0.5102; εNd values correspondingly range from +1 to -10. Sr and Nd isotopic values of similar range are also reported from 1.88 Ga BD2 dykes in Bastar craton (Srivastava et al, 2009) and Bijawar igneous units (Pandey et al, 2012). In a Sr-Nd isotope plot (figure not shown), the Proterozoic mafic samples strikingly differ from the mantle components defined by Hart and Zindler (1989).…”
Section: Geochemistry and Petrological Featuressupporting
confidence: 75%
“…It is known that the early earth was hotter and therefore mafic magmatic activities were rampant and various estimates indicate that nearly 80% of the crust was formed during the Archaean [3,5]. It is observed that the mafic volcanic rocks were preserved in the greenstone belts or Precambrian continental rift basins [6,7], but in most of the cratons where the basement gneisses are exposed, we observe only the dykes and dyke swarms and no volcanic equivalents are observed because of severe erosion to the deeper levels exposing the basement rocks [8][9][10][11][12]. It is possible that during the early earth there were numerous LIPs and their equivalents were present but these got eroded with time [13][14][15][16].…”
Section: Introductionmentioning
confidence: 61%
“…Granulites from Balaghat-Bhandara and Ramakona-Katangi Ganulite belts associated with Central Indian Suture (CIS) zone [41,28] and Bhopalpatnam and Karimnagar granulite belts are exposed in Western Bastar [36,[42][43][44][45][46]. Mafic dyke swarms of Bastar Craton include NWSE trending Keshkal swarm, Bhanupratappur swarm, Dantewara swarm, and Bastanar swarm, NNW-SSE trending Sonakhan swarm, N-S trending Lakhna dykes, ENE-WSW trending Bandimal dykes are well studied [11,22,42,[47][48][49][50][51][52][53][54][55][56][57]. Dongargarh, Malanjkhand, Abhujmar and Mul granites represent the diverse Proterozoic granites from Bastar Craton [37,56,[58][59][60][61][62].…”
Section: Regional Geologymentioning
confidence: 99%
“…The juvenile nature of the samples is established in Figure 9a, where they plot close to the depleted mantle curve and are also widely separated from the Nd isotopic evolutionary trend of Archean crust. The positive ε Nd values for some of the rocks suggest their derivation from a depleted mantle source (Srivastava et al 2009). The range of initial ε Nd values from our samples strongly suggests that the rocks were produced entirely from the mantle in an oceanic setting (DePaolo, 1988), with possible minor crustal contamination.…”
Section: B Petrogenesis Of the Metavolcanic Rocks And Enclavesmentioning
confidence: 70%